Developing organization-wide BPM capabilities in an SME : the approaches used, challenges and outcomes - Bandara, Wasana; Opsahl, Hanna (London : Palgrave MacMillan UK, 2017)
Business Process Management (BPM) is well known for improving the competitiveness and sustainability of a business, and is widely applied. But, BPM practices in SMEs are alarmingly low, regardless of the potential positive impacts BPM brings. This is due to: limited resources, absence of a cross-functional mindset and lack of strategic clarity. Adopting BPM as a management paradigm across the enterprise [hereafter referred to as Enterprise-BPM (E-BPM)] reduces operational inefficiencies and supports innovative practices essential for success, which is the key to SMEs. However, SMEs lack the required know-how, and hence, BPM education/training plays a vital role in supporting this transformation. This case is based on a Norwegian conference venue operating in the Norwegian market. This narrative describes the organization, the context for deploying BPM on enterprise-level and related challenges.
Originally Published InBandara, W., & Opsahl, H. (2017). Developing organization-wide BPM capabilities in an SME: the approaches used, challenges and outcomes. Journal of Information Technology Teaching Cases, 7, 92–113.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Workflow -- Management; Small business -- Management